Geometric model and assessment of a dual-fisheye imaging system - Campos, Mariana Batista [UNESP]; Tommaselli, Antonio Maria Garcia [UNESP]; Marcato Junior, José; Honkavaara, Eija (Wiley, 2018)
This paper presents a technique for the calibration of a 360° dual imaging system (Ricoh Theta S) composed of two cameras with fisheye lenses specially mounted in a common structure. The experiments are based on calibration with a bundle adjustment using the equidistant fisheye lens model and relative orientation stability constraints, such as distance, base elements and rotation matrix between individual cameras’ coordinate systems. As a result, an equidistant mathematical model using the Conrady–Brown lens distortion model was shown to be suitable for estimating the interior and relative orientation parameters of the Ricoh Theta S. The main contribution presented in this work is a simultaneous bundle adjustment approach with stability constraints on base elements and rotation matrix angles, which achieved accuracies comparable with conventional photogrammetric calibration with perspective cameras.
Keywords: camera calibration; fisheye lenses; interior orientation parameters; omnidirectional systems; polydioptric spherical imaging systems; Ricoh Theta S